Alcohol Sponsorship and Esports: Reinforcing the Need for Legislative Restrictions on Alcohol Sponsorship. (8th January 2020) - Chambers, Tim
Abstract: Alcohol sponsorship in esports is on the rise. Many esports athletes and viewers are children and young people. Alcohol sponsorship of esports places millions of children and young people at risk of alcohol-related harm. Action on alcohol sponsorship in esports may provide policy makers an opportunity for greater restrictions on all alcohol sports sponsorship.